2021
DOI: 10.5194/acp-21-14749-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced volatility of aerosols from surface emissions to the top of the planetary boundary layer

Abstract: Abstract. Aerosols from surface emission can be transported upwards through convective mixing in the planetary boundary layer (PBL), which subsequently interact with clouds, serving as important sources to nucleate droplets or ice particles. However, the evolution of aerosol composition during this vertical transport has yet to be explicitly understood. In this study, simultaneous measurements of detailed aerosol compositions were conducted at two sites, namely urban Beijing (50 m above sea level – a.s.l.) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This, in turn, implied that there was a more important fraction of nitrogenous OA on the mountain than on the surface. The reduced fraction of inorganic nitrate, which has been reduced, is consistent with our previous study, which found that ammonium nitrate evaporated during vertical transport due to its higher volatility 28 .…”
Section: Enhanced Fraction Of Nitrogenous Organic Aerosols After Agin...supporting
confidence: 92%
See 1 more Smart Citation
“…This, in turn, implied that there was a more important fraction of nitrogenous OA on the mountain than on the surface. The reduced fraction of inorganic nitrate, which has been reduced, is consistent with our previous study, which found that ammonium nitrate evaporated during vertical transport due to its higher volatility 28 .…”
Section: Enhanced Fraction Of Nitrogenous Organic Aerosols After Agin...supporting
confidence: 92%
“…Previous research has observed that surfaceemitted pollutants mix with the convective boundary layer during the day and reach mountainous sites on a daily basis. Effective transport or formation of low-volatile substances from the ground to the top of the PBL was observed; however, semi-volatile substances decreased during the upward transport process 28 .…”
Section: Sampling Sitementioning
confidence: 94%
“…The enhanced solar radiation under C2 and C3 decreased the nitrate concentration with aging time, possibly due to the lack of NO x (Figure S9b in Supporting Information ). Higher temperature/lower RH or dilution during transport (Liu et al., 2021) may cause the evaporation of ammonium nitrate as nitric acid and ammonia in the gas phase due to its semi‐volatile nature (Aw & Kleeman, 2003; Liu et al., 2021). The aqueous‐phase process under high RH in C1 favored the partitioning of ammonium nitrate in the particulate phase.…”
Section: Resultsmentioning
confidence: 99%
“…4). After transport, the fractional contribution of sulfate increased from 17 % (3.8 µg m −3 ) to 26 % (5.6 µg m −3 ) in the urban GZB transport pathway and from 20 % (6.2 µg m −3 ) to 32 % (9.9 µg m −3 ) in the BTH transport pathway, while the nitrate fraction increased from 12 % (2.7 µg m −3 ) to 19 % (3.7 µg m −3 ) in the urban GZB transport pathway but slightly decreased from 24 % (7.4 µg m −3 ) to 19 % (5.9 µg m −3 ) in the BTH transport pathway likely due to the mass loss of semi-volatile aerosol species (such as NH 4 NO 3 ) when aerosols are exposed to a cleaner environment during long-distance transport (Liu et al, 2021). We also compared the pollution episodes caused by the continuous transport from the BTH (EP1) and the urban GZB (EP2) (as shown in the shaded area in Fig.…”
Section: Secondary Inorganic Formation During the Transportmentioning
confidence: 95%